If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3x + 5) = -24 Reorder the terms: 6(5 + 3x) = -24 (5 * 6 + 3x * 6) = -24 (30 + 18x) = -24 Solving 30 + 18x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 18x = -24 + -30 Combine like terms: 30 + -30 = 0 0 + 18x = -24 + -30 18x = -24 + -30 Combine like terms: -24 + -30 = -54 18x = -54 Divide each side by '18'. x = -3 Simplifying x = -3
| 5x+10=7x+26 | | 8-18=z/-7= | | 3=xx+3-5x | | 2v+17=47 | | w-144=-11 | | 2x+1=3+x | | 3x-21y=-24 | | y-(-99)=4 | | 5x+9=-3+7x | | 6.5x-3=11 | | 1-6x=5x+1 | | k-7=-12 | | -2(-2-4n)-4n=-2+5(n+3) | | -7x+5=115+3x | | 1-2x=7x+10 | | -12+x=23 | | 4x^2+2x+16=0 | | 3x+1=-19+x | | 4y*1*9*7y= | | 4g+13500=8500 | | 5x-4(-x+1)=-7 | | 3m-12=36 | | 14u-18v= | | n/9=18 | | 0.6x+11.4=x-5.32 | | 5(9+6x)+7=-12+14x | | -18+9a=8(1+a)-13 | | 10xy-4y= | | 12(v-13)=2v-66 | | 4t^2+24t-27=0 | | 24+y*2=x | | -25=4(5k-7)+3(1+3k) |